Морфологический анализ повреждений генеративных органов Salvia officinalis L. при интродукции в условиях Донбасса - Горлачева, З.С. (Донецький ботанічний сад НАН України, 2009)
Изучены различные формы повреждения генеративных органов разных образцов Salvia officinalis L. в условиях интродукции Донецкого ботанического сада. По степени повреждения все образцы распределены на семь групп, определены и описаны типы повреждений генеративных органов S. officinalis. Анализ полученных данных показал, что наиболее чувствительными к воздействию отрицательных факторов оказались размеры тычиночной нити и связника, а также наличие сросшихся нижних пыльников. Следовательно, характеристика строения тычиночного аппарата может являться показателем устойчивости S. officinalis к низким температурам. Various forms of injuries to generative organs of different samples of Salvia officinalis L. in the conditions of their introduction into Donetsk Botanical Garden have been studied. All the samples have been divided into seven groups according to the degree of injuries; the types of injuries to the generative organs of S. officinalis L. have been defined and described. An analysis of the data obtained has shown that the plant sensitivity to the influence of negative factors is determined by the size of the stamen filament and the connective, and the presence of the adnated lowest anthers. Therefore, the characteristics of the structure of the staminal apparatus can serve as an indicator of stability of S. officinalis to low temperatures.